Increasing Role of Roof Gutters as Aedes aegypti (Diptera: Culicidae) Breeding Sites in Guadeloupe (French West Indies) and Consequences on Dengue Transmission and Vector Control. (2nd April 2012) - Gustave, Joël; Fouque, Florence; Cassadou, Sylvie; Leon, Lucie; Anicet, Gabriel; Ramdini, Cédric; Sonor, Fabrice
Abstract : During the past ten years, the islands of Guadeloupe (French West Indies) are facing dengue epidemics with increasing numbers of cases and fatal occurrences. The vector Aedes aegypti is submitted to intensive control, with little effect on mosquito populations. The hypothesis that important Ae. aegypti breeding sites are not controlled is investigated herein. For that purpose, the roof gutters of 123 houses were systematically investigated, and the percentage of gutters positive for Ae. aegypti varied from 17.2% to 37.5%, from humid to dry locations. In the dryer location, most of houses had no other breeding sites. The results show that roof gutters are becoming the most important Ae. aegypti breeding sites in some locations in Guadeloupe, with consequences on dengue transmission and vector control.